CHARACTERIZATION AND ANALYSIS OF GULLY EROSION IN SOUTHERN BRAZIL WITH THE ASSISTANCE OF UNMANNED AERIAL VEHICLE - Rademann, Lucas Krein; Trentin, Romario; Robaina, Luis Eduardo de Souza (Mercator, 2023)
The ability to understand the erosive mechanisms of a gully is of great importance for determine its dynamics and the best forms of intervention. Thus, with the assistance of high-resolution data obtained with UAV, this work seeks to characterize and analyse the erosive mechanisms that act in a gully in south Brazil. For this, a survey was carried out using a multirotor UAV, with a flight height of 150m, and an overlaid area of 67ha. The data obtained were processed using the SfM-CMVS (Structure from Motion - Clustering Multi-View Stereo) workflow, generating a Digital Terrain Model with a spatial resolution of 12,6 cm/pixel. However, mass movements proved to be the main lateral and vertical advancement agent of the gully, predominating in the upper portions of the gully. In the lower third of the gully there was a predominance of mass movements and lowering areas related to the contact of sandy rock lenses with more clayey lenses. The products generated in this work provide a database that has the potential to assist in work to be developed, serving as a basis for the study of gully genesis, for the identification of the best mitigation measures, or as an initial framework for the study of evolution of this erosive feature. So, make it necessary more in-depth study of the real impacts of silviculture on erosive mechanisms. Keywords : Gully Erosion, Structure From Motion–Multi-View Stereo (SfM–MVS), Erosion Mechanisms, Mass Movements.